Comparative evaluation of the results of antibiotic prophylaxis of early postoperative complications of transurethral resection of the prostate in patients with benign prostatic hyperplasia - Vlasyk , Marharyta; Nikitin , Oleg; Nasheda , Serhiy; Samchuk, Pavlo (The Ukrainian Scientific Medical Youth Journal, 2023)
in Ukraine in 2021, the incidence of benign prostatic hyperplasia (BPH) was 321.6 per 100,000 population. Almost 17,000 operations on prostate gland have been performed, a significant proportion of which are transurethral resection (TURP). It has been proven that the most frequent early complications after surgical interventions on the prostate gland are the development of an acute inflammatory process in the genitourinary organs, bleeding from the area of there removed hyperplastic tissue of the prostate gland. Inflammatory diseases of the urogenital tract in men are characterized by a variety of etiological agents, the presence of mixed infections, and the growing importance of pathogens of sexually transmitted diseases. To improve the results of TURP in patients with BPH complicated by acute urinary retention by optimizing antibacterial prophylaxis of postoperative complications in the early postoperative period. The study is based on the results of the analysis of surgical treatment of 179 patients with BPH complicated by acute urinary retention who underwent TURP. The age of the patients varied from 51 to 84 years, the average age was 64.9±5.1 years. Patients were divided into two groups: Group I – 85 operated patients who were prescribed ceftriaxone (1.0 parenterally once a day) in the early postoperative period; Group II – 94 patients, in the early postoperative period got levofloxacin (500 mg IV for 3-5 days with subsequent transition to oral administration, once a day). The analysis of the obtained data established that in the early postoperative period 43 (24.1%) patients had complications. The most frequent complication was long-term macrohematuria, which was observed in 23 (12.9%) patients. Exacerbation of chronic pyelonephritis occurred in 13 (7.3%) operated patients, acute urethritis developed in 7 (3.9%) patients, acute orchiepididymitis was observed in 9 (5.0%) patients. The over all frequency of complications in patients with BPH who received levofloxacin in the early postoperative period was statistically significantly lower than in patients who were prescribed ceftriaxone. In particular, the use of levofloxacin in patients of the II group, with the aim of antibiotic prophylaxis of postoperative complications after TURP, made it possible to reduce the frequency of the latter by 60% (1.6 times), in relation to the patients of the I group. The use of levofloxacin for the prevention of early postoperative complications after TURP inpatients with BPH complicated by acute urinary retention improves the results of surgical treatment by reducing the frequency of complications in the postoperative period by 60%.